2007
DOI: 10.1007/s11104-007-9280-y
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation dynamics of soil carbon and nitrogen by wheat roots and Collembola

Abstract: It has been demonstrated that plant roots can take up small amounts of low-molecular weight (LMW) compounds from the surrounding soil. Root uptake of LMW compounds have been investigated by applying isotopically labelled sugars or amino acids but not labelled organic matter. We tested whether wheat roots took up LMW compounds released from dual-labelled ( 13 C and 15 N) green manure by analysing for excess 13 C in roots. To estimate the fraction of green manure C that potentially was available for root uptake,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…This is convincingly exemplified for the best studied group of soil fungivores, the Collembola (Larsen et al 2007;Ostle et al 2007). By tracing 13 C-signatures of grasses in grassland soil Jonas et al (2007) have shown that depending on soil type and plant species, saprophytic fungi made up between 40-80%, while arbuscular mycorrhizal fungi constituted up to 60% of the collembolan diet, respectively.…”
Section: Rhizodeposition and Interactions Of Rhizosphere Fauna With Mmentioning
confidence: 67%
See 1 more Smart Citation
“…This is convincingly exemplified for the best studied group of soil fungivores, the Collembola (Larsen et al 2007;Ostle et al 2007). By tracing 13 C-signatures of grasses in grassland soil Jonas et al (2007) have shown that depending on soil type and plant species, saprophytic fungi made up between 40-80%, while arbuscular mycorrhizal fungi constituted up to 60% of the collembolan diet, respectively.…”
Section: Rhizodeposition and Interactions Of Rhizosphere Fauna With Mmentioning
confidence: 67%
“…In contrast to conventional wisdom, recent evidence suggest that a major part of the soil animal food web strongly relies on the C-inputs from plant roots and less so on the carbon and nutrient inputs via leaf litter (Albers et al 2006;Larsen et al 2007;Pollierer et al 2007), but see Elfstrand et al (2008). Therefore special attention must be given to the consumers of microorganisms in the rhizosphere, because they are at the base of the soil food web channeling the energy to the higher trophic levels via two distinct routes, the fungal and the bacterial energy channel (Moore and Hunt 1988) and determine the rates of nutrient cycling and the availability of mineral nutrients to plants (Clarholm 1985;Kuikman et al 1990;Ekelund and Rønn 1994;Laakso and Setälä 1999;Bonkowski 2004).…”
Section: Rhizodeposition and Interactions Of Rhizosphere Fauna With Mmentioning
confidence: 99%
“…Amino acid exchange may also occur in symbiotic associations between plants and fungi, a situation in which each partner has the ability to synthesize amino acids but fungi may also absorb amino acids from the substrate (Read andPerez-Moreno 2003, Brundrett 2004). A marker of amino acid biosynthetic origin would be a powerful tool for investigations of amino acid exchange in symbiotic and trophic relationships, as well as a way to monitor diet in organisms that are otherwise intractable for studies of foraging behavior such as soil microarthropods (Chahartaghi et al 2005, Larsen et al 2007). Here we present a new approach to tracing the origins of amino acids: using unique patterns of carbon isotope signatures generated by amino acid synthesis in plants, fungi, and bacteria (here termed a '' 13 C fingerprint'').…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of collembolan feeding habits at the species or functional group level is steadily increasing (Chamberlain et al, 2006;Ngosong et al, 2011;Ruess et al, 2007;Sechi et al, 2014a), but several gaps still exist. It is known that Collembola are closely associated with the rhizosphere food web being nutritionally supported by root-derived resources (Endlweber et al, 2009;Larsen et al, 2007;Sabais et al, 2012Larsen et al 2016b), but the path through which they obtain these resources is not yet clear. While euedaphic and hemiedaphic species have been shown to incorporate recent photosynthate carbon (C) from crops (Larsen et al, 2007;Ostle et al, 2007), A.M. recently demonstrated that only a fraction of these plant derived resources derives from direct foraging on roots.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that Collembola are closely associated with the rhizosphere food web being nutritionally supported by root-derived resources (Endlweber et al, 2009;Larsen et al, 2007;Sabais et al, 2012Larsen et al 2016b), but the path through which they obtain these resources is not yet clear. While euedaphic and hemiedaphic species have been shown to incorporate recent photosynthate carbon (C) from crops (Larsen et al, 2007;Ostle et al, 2007), A.M. recently demonstrated that only a fraction of these plant derived resources derives from direct foraging on roots. Hence, Collembola are influenced by plant-related changes that affect availability, quality and palatability of microbial derived food sources.…”
Section: Introductionmentioning
confidence: 99%